2018
DOI: 10.1074/jbc.ra118.002926
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of mitochondrial calcium uniporter incompletely inhibits calcium uptake and induction of the permeability transition pore in brain mitochondria

Abstract: Ca influx into mitochondria is mediated by the mitochondrial calcium uniporter (MCU), whose identity was recently revealed as a 40-kDa protein that along with other proteins forms the mitochondrial Ca uptake machinery. The MCU is a Ca-conducting channel spanning the inner mitochondrial membrane. Here, deletion of the MCU completely inhibited Ca uptake in liver, heart, and skeletal muscle mitochondria. However, in brain nonsynaptic and synaptic mitochondria from neuronal somata/glial cells and nerve terminals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 66 publications
6
41
0
Order By: Relevance
“…Consistent with this result, we found that both WT and mcu -/- cones have a population of mitochondrial clusters which still appear to take up Ca 2+ even in the presence of the MCU inhibitor Ru360, and the characteristics of this population match those of the responding mitochondria in mcu -/- cones. This is similar to what has been observed in non-synaptic brain mitochondria isolated from Mcu -/- mice, in which uptake of Ca 2+ into mitochondria was not blocked but instead occurred at a slower rate compared to controls 20 . Taken together, these results suggest that that neuronal tissue like retina and brain may have an alternative mitochondrial Ca 2+ uptake pathway with different response kinetics and Ca 2+ uptake capacity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with this result, we found that both WT and mcu -/- cones have a population of mitochondrial clusters which still appear to take up Ca 2+ even in the presence of the MCU inhibitor Ru360, and the characteristics of this population match those of the responding mitochondria in mcu -/- cones. This is similar to what has been observed in non-synaptic brain mitochondria isolated from Mcu -/- mice, in which uptake of Ca 2+ into mitochondria was not blocked but instead occurred at a slower rate compared to controls 20 . Taken together, these results suggest that that neuronal tissue like retina and brain may have an alternative mitochondrial Ca 2+ uptake pathway with different response kinetics and Ca 2+ uptake capacity.…”
Section: Discussionsupporting
confidence: 89%
“…MCU has been widely thought to be the sole route of Ca 2+ entry into mitochondria in eukaryotes, as loss of MCU completely inhibits mitochondrial Ca 2+ uptake in skeletal muscle, liver, heart, brown adipose tissue, and a wide variety of cell lines 15 19 . Despite this, it is possible that certain specialized cell types might not rely solely on MCU for mitochondrial Ca 2+ uptake, since it also has been observed that brain mitochondria lacking MCU expression do not have a complete loss of mitochondrial Ca 2+ uptake 20 . Thus, the role that MCU plays in vertebrate photoreceptors remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria accumulate large amounts of Ca 2+ and contribute to the maintenance of a low resting [Ca 2+ ] i (Foskett and Philipson, 2015): if [Ca 2+ ] i exceeds a threshold in the micromolar range, cells trigger metabolic pathways leading to cell death (Liu et al, 2015). Ca 2+ influx into mitochondria is mediated by mitochondrial Ca 2+ uniporter (MCU), and genetic ablation of Mcu decreases mitochondrial Ca 2+ uptake (Hamilton et al, 2018), while persistent MCU activity enhances mitochondrial Ca 2+ uptake (Dong et al, 2017). It has been proposed that cancer stem cells share several properties of adult neural stem cells, in particular altered Ca 2+ regulation (Leclerc et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the activation of Na + /K + -ATPase rapidly reduces intracellular energy stores and causes neurons to produce more energy in a quick but inefficient way, namely, glycolysis [ 13 ]. Concurrently, oxidative metabolism is disrupted to overproduce reactive oxygen and nitrogen species (ROS and RNS, respectively) [ 12 , 14 ] and increase mitochondrial permeability [ 15 , 16 , 17 ], leading to further loss of neurons and associated functions. Therefore, ion channels are a candidate target for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%